The Performance of a Spherical-tip Catheter for Stent Post-dilation: Finite Element Analysis and Experiments - Qi, Lin; Zhu, Wenbo; Qian, Wei; Xu, Lisheng; He, Ying; Zhao, Feihu (Frontiers in Physiology, 2021)
At present, percutaneous coronary intervention (PCI) is the most effective treatment of coronary artery stenosis. However, in case post-dilation of the stent is needed, the tip of the commonly used post-dilation balloon catheter cannot always pass through the stent smoothly, especially when it is situated in curved part of the vessel. To improve the performance of traditional post-dilation balloon catheter, a preliminary design of a novel catheter with a spherical tip is proposed. Since the performance of this spherical-tip catheter is still unclear, in this study, finite element analysis (FEA) and experimental validation of blood vessel with different curvature radii were performed to test and evaluate the performance of the spherical-tip catheter design. The comparative results between two types of catheters demonstrate that in the simulated post-dilation process, the spherical-tip catheter is easier to pass through the stent placed in the curved vessel without the deformation of the stent strut, and can theoretically reduce the operation time and improve the safety of the operation. Furthermore, the strong consistency between simulation and experiment indicates that the finite element (FE) model can be a useful tool for future optimization and evaluation of novel catheters, so as to save time and budget in product development and reduce/replace animal studies.